2001
DOI: 10.1136/pmj.77.907.320
|View full text |Cite
|
Sign up to set email alerts
|

Management of the impalpable testis: a six year review together with a national experience

Abstract: The management of undescended testes remains variable, and the use of laparoscopy for localisation is controversial. This study reviews the need for laparoscopy and also assesses the current practice among a cohort of surgeons.A retrospective review of all patients undergoing orchidopexy was performed, together with a postal survey of all members of the Welsh Surgical Society.Of the 139 orchidopexies performed, the testis was deemed impalpable in 39 (28%) cases. All patients were treated with groin exploration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 13 publications
0
26
0
1
Order By: Relevance
“…The accuracy rates of diagnosis and localization of a nonpalpable testis with MRI (85%) and ultrasound (84%) are nearly equally with no statistically significant differences (13,14). Diagnostic laparoscopy has been established as the most reliable diagnostic technique for localizing nonpalpable testes with nearly 100% sensitivity and specificity (1,(14)(15)(16), However, it is an invasive technique.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The accuracy rates of diagnosis and localization of a nonpalpable testis with MRI (85%) and ultrasound (84%) are nearly equally with no statistically significant differences (13,14). Diagnostic laparoscopy has been established as the most reliable diagnostic technique for localizing nonpalpable testes with nearly 100% sensitivity and specificity (1,(14)(15)(16), However, it is an invasive technique.…”
Section: Introductionmentioning
confidence: 97%
“…Undescended testis or cryptorchidism, a condition in which one or both testicles are not appropriately positioned in the scrotum at birth (1). It is the most common congenital genitourinary anomaly in boys and has an incidence of 1-3% in term and 15-30% in premature male infants (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…al. reported that in 37 of impalpable testes, inguinal exploration was suffi cient for deciding and executing treatment 15 . Adam and Allaway reported good results with inguinal exploration followed by intraperitoneal approach for 110 impalpable testes.…”
Section: Discussionmentioning
confidence: 99%
“…Beide Methoden sind als gleichwertig zu betrachten. Da in etwa 5% der Fälle die Operation mit dem ge wählten Verfahren nicht erfolgreich been det werden kann, sollte während des Ein griffs auf das jeweils andere Verfahren ge wechselt werden können [35,36]. Bei 9,8% der Jungen wird bei abdominalen Hoden eine Hodenaplasie diagnostiziert [13].…”
Section: Operative Therapieunclassified